Study on the Different Effects of Power and Trailer Wheelsets on Wheel Polygonal Wear - X. N. Zhao; G. X. Chen; Z. Y. Huang; C. G. Xia (Shock and Vibration)
The wheels of power and trailer wheelset show different polygonal characteristics since their structures are obviously different. Therefore, the frictional self-excited vibration models of wheelset-track systems are established based on the viewpoint of the frictional self-excited vibration in reducing the wheel polygonal wear. Then, the motion stability of wheelset-track systems is studied by using the complex eigenvalue method. The results show that when the creep force between the wheel and rail is saturated, the unstable vibration frequency of the power wheelset is prone to induce 19-20th-order polygonal wear of the wheel, and the trailer wheelset is prone to induce 20-21th-order polygonal wear of the wheel. Meanwhile, the wheel polygonal wear can be effectively alleviated through changing the gearbox position of the power wheelset. And avoiding disc braking at high speeds can suppress the occurrence of wheel polygonal wear. In addition, the development tendency of wheel polygonal wear can be reduced by increasing the Young’s modulus of the brake pad, but Poisson’s ratio has little effect on the development tendency.